Notas sobre el cacique Libânio y el barón de Antonina en los aldeamientos indígenas de las provincias meridionales del Brasil Imperial (1840-1889) - Pablo Antunha Barbosa (Nuevo mundo - Mundos Nuevos, 2013)
The cacique cayuá Libânio is a central figure in the construction of the indigenous missions in the provinces of São Paulo, Paraná and Mato Grosso that were instituted in 1845 by Regulation n. 426 on "Catechesis and civilization of the Indians". Managed from the capitals of the provinces by the military and in the field by the Capuchin missionaries, the indigenous missions were planned within a much broader project: that of the colonization of the frontiers and that of the unknowns "sertões" of the Empire. The indigenous missions were spatially associated with military and agricultural colonies that worked during the War of the Triple Alliance (1864-1870) as an advanced system of colonial and military deployment. From biographical elements of the life of cacique Libânio, this paper aims to analyze the forms of mediation practiced by him among indigenous missions newly created and Guarani camps that were located in the Paraná River basin, Tibagi, Paranapanema, Brilhante and Iguatemi. Libânio, the main Indian guide of "Southern Journeys", function as a central figure in the formation and in the consolidation of these establishments; while the expeditions were moving through the hinterland, Libânio drives and activates a series of networks and alliances, driving every year a significant quantity of indigenous families to be established in the orbit of the missions.